PERTUMBUHAN DAN HASIL PANEN TANAMAN JAGUNG (Zea mays) VARIETAS LOKAL DAN HIBRIDA YANG DI INFEKSI CENDAWAN Fusarium sp - D.A. Trifatmawati; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2018)
The aim of this study to prove the effect of Fusarium sp fungus infection on corn (Zea mays) to the growth and yield of local corn varieties and hybrid corn varieties. After the age of 45 HST treatment done 5 polybags of plants local corn varieties and 5 polybags of plant hybrid corn varieties infected with Fusarium sp fungus and 5 polybags of plants local corn varieties and 5 polybags of plant hybrid corn varieties not infected by fungus Fusarium sp. The result showed that treatment infected of Fusarium sp and without Fusarium sp fungus significant (P <0,05) to growth and yield of local varieties and hybrid varieties of corn. The average height of local varieties and hybrid varieties of corn with infected by Fusarium sp significant (P <0.05) was lower than the height of corn without Fusarium sp fungus. Local and hybrid varieties of corn after being infected with Fusarium sp fungus showed results significant of leaf with. The yield of corn and the weight of kernel that has been shell showed treatment of Fusarium sp (F5) fungus significant (P <0,05) was lower than the yield of corn not infected by Fusarium sp. The results of this study can be concluded that infections of Fusarium sp fungus on local varieties and hybrid varieties have an influence on growth and yield. Keyword : Corn, Fusarium sp, growth and yield